Does thoracoscopic basal pyramid segmentectomy really offer functional advantages in comparison with thoracoscopic lower lobectomy?. Issue 2 (25th January 2023) - Bongiolatti, Stefano; Salvicchi, Alberto; Mugnaini, Giovanni; Vokrri, Eduart; Viggiano, Domenico; Gonfiotti, Alessandro; Lavorini, Federico; Voltolini, Luca
Abstract: OBJECTIVES: The functional impact of thoracoscopic basal segmentectomy in comparison with lower lobectomy has not been investigated in-depth and the aim of this study was to clarify this topic. METHODS: We retrospectively analysed a cohort of patients who underwent surgery between 2015 and 2019 for non-small-cell lung cancer, peripherally located lung nodules, far enough from both the apical segment and the lobar hilum to allow an oncologically safe thoracoscopic lower lobectomy or basal segmentectomy. Pulmonary function tests (PFTs) including spirometry and plethysmography were performed 1 month after surgery and forced expiratory volume in 1 s, forced vital capacity (FVC) and diffusing capacity for carbon monoxide (DLCO) were collected; the difference, the loss and the recovery rate of pulmonary function were calculated and compared with the Wilcoxon–Mann–Whitney test. RESULTS: During the study period, n = 45 and n = 16 patients for video-assisted thoracoscopic surgery (VATS) lower lobectomy and for VATS basal segmentectomy, respectively, completed the study protocol: the 2 groups were homogeneous as to preoperative variables and PFT values. Postoperative outcomes were similar and PFTs revealed significant differences between postoperative forced expiratory volume in 1 s %, FVC%, ΔFVC and ΔFVC%. The loss percentage of FVC%, DLCO% and the recovery rate was better for FVC and DLCO in the VATS basal segmentectomy group. CONCLUSIONS: Thoracoscopic basal segmentectomy seems to be associated with a more preserved lung function, maintaining more FVC and DLCO levels than lower lobectomy, and could be performed in selected cases ensuring also adequate oncological margins. Abstract : Lobectomy and systematic lymph node dissection is the standard treatment for early-stage non-small-cell lung cancer (NSCLC) according to the results of a prospective randomized multi-institutional trial conducted by the Lung Cancer Study Group in 1995 [1] which showed that sublobar resection has a significative increased risk of recurrence compared to lobectomy.